Predictors of mortality among children at a tertiary hospital in Tanzania: a cohort study - Diana K. Damian; Francis F. Furia; Germana Leyna (SpringerOpen, 2024)
Abstract Background Tanzania is among the countries in sub-Saharan Africa with the highest under-five mortality rate. The leading causes of mortality among these children include vaccine-preventable infections. Strategies for reducing under-five mortality in hospital settings require a good knowledge of driving factors, which are largely unknown in Tanzania. This study was conducted at Muhimbili National Hospital to determine mortality and its predictors among under-five admitted in the general paediatric wards. Methods We conducted a prospective cohort study among children aged between 1 and 59 months admitted in the paediatric wards at Muhimbili National Hospital from 2nd October 2017 to 13th April 2018. We recruited eligible children consecutively and followed them up until discharge or death. We calculated the mortality rate as the incidence density rate and determined the causes and predictors of mortality. We analyzed data to identify and quantify predictors of deaths and used Kaplan-Meir and Cox regression analyses to determine predictors of survival. A P-value of < 0.05 was considered statistically significant. Results We recruited 925 children aged 1-59 months with a median age of 13 and (IQR) of (20) months, females constituted 40.8%. The overall mortality rate was 12.2% (95% CI: 10.2%-14.5%). We found septicaemia (27%), malnutrition (12%), congenital heart disease (12%), pneumonia (11%), and Human Immunodeficiency Virus infection (9%) to be leading causes of mortality. More deaths were observed at night, during the first 24 h of admission, and on weekends. Independent factors for mortality were found to be low wealth quintiles (lowest quintile (AOR = 4.0; 95% CI: 1.19-13.51), second quintile (AOR = 5.2; 95% CI: 1.65-16.69) and middle quintile (AOR = 3.6; 95% CI: 1.14-11.33), unconsciousness on admission (AOR = 18; 95% CI: 6.70-56.82), inability to feed (AOR = 5.7; 95% CI: 1.97-16.51), lethargy (AOR = 4.9; 95% CI: 2.32-10.40), severe wasting (AOR = 4.5; 95% CI: 2.49-8.10), and respiratory distress (AOR = 2.6; 95% CI: 1.40-4.97). Conclusion A high mortality rate was noted in this study and low wealth quantile, low parental education, and lack of health insurance were associated with high mortality. Patients had the highest risk of mortality within 24 h of admission, therefore it is important to raise awareness among clinicians regarding the need for improvement in the monitoring of patients, especially within 24 h of admission.